Modern transformations in desert environments: Population and agricultural development projects in the areas of Umm al-Aranib, Al-Hamirah and Zuwaylah: Modern transformations in desert environments: Population and agricultural development projects in the areas of Umm al-Aranib, Al-Hamirah and Zuwaylah (jornal of the libyan geographical society, 1997)
In a serious attempt to break free from the clutches of backwardness and shake off the dust of the past, the desert environments in Libya have taken great strides on the path of development, striving to achieve a kind of developmental balance with the flourishing coastal strip, and have revived their artistic history.The city prepared itself for construction and development with all its resources, embracing vital agricultural and urban projects that formed the foundation for advancement, development, and modernization. It looked to the future with great self-confidence and high hopes for further growth and the creation of new economic, social, and cultural structures.
Keywords: desert environments; Developmental balance; Vital projects; Urbanism; agriculture